Channel response to a dam‐removal sediment pulse captured at high‐temporal resolution using routine gage data. Issue 6 (29th March 2021) - Cashman, Matthew J.; Gellis, Allen C.; Boyd, Eric; Collins, Mathias J.; Anderson, Scott W.; McFarland, Brett D.; Ryan, Ashley M.
Abstract: In this study, we captured how a river channel responds to a sediment pulse originating from a dam removal using multiple lines of evidence derived from streamflow gages along the Patapsco River, Maryland, USA. Gages captured characteristics of the sediment pulse, including travel times of its leading edge ( 7.8 km yr −1 ) and peak ( 2.6 km yr −1 ) and suggest both translation and increasing dispersion. The pulse also changed local hydraulics and energy conditions, increasing flow velocities and Froude number, due to bed fining, homogenization and/or slope adjustment. Immediately downstream of the dam, recovery to pre‐pulse conditions occurred within the year, but farther downstream recovery was slower, with the tail of the sediment pulse working through the lower river by the end of the study 7 years later. The patterns and timing of channel change associated with the sediment pulse were not driven by large flow or suspended sediment‐transporting events, with change mostly occurring during lower flows. This suggests pulse mobility was controlled by process‐factors largely independent of high flow. In contrast, persistent changes occurred to out‐of‐channel flooding dynamics. Stage associated with flooding increased during the arrival of the sediment pulse, 1 to 2 years after dam removal, suggesting persistent sediment deposition at the channel margins and nearby floodplain. This resulted in National Weather Service‐indicated flood stages being attained by 3–43% smaller discharges compared to earlier in the study period. This study captured a two‐signal response from the sediment pulse: (1) short‐ to medium‐term (weeks to months) translation and dispersion within the channel, resulting in aggradation and recovery of bed elevations and changing local hydraulics; and (2) dispersion and persistent longer‐term (years) effects of sediment deposition on overbank surfaces. This study further demonstrated the utility of US Geological Survey gage data to quantify geomorphic change, increase temporal resolution, and provide insights into trajectories of change over varying spatial and temporal scales. Abstract : We leverage routine streamflow gage data to track channel changes associated with a sediment pulse originating from a dam removal. We capture at high‐temporal resolution: pulse characteristics such as travel times, translation and dispersion, aggradation and recovery of bed elevation, changing local hydraulics, and deposition on overbank surfaces.